ANALISIS PELAKSANAAN LITERASI BACA DAN TULIS SISWA KELAS IV SD NEGERI 1 NGROPOH TEMANGGUNG - Angga Ibnu Miftah Nurfauzan; Filia Prima Artharina; A. Y. Soegeng Ysh (STKIP Subang, 2023)
Literacy is seen as the ability to read and write. Literacy understanding then begins to develop into language skills, which include the ability to read, write, speak and listen. Over time, the definition of literacy has expanded to encompass a variety of scientific disciplines. The focus of this research is how is the implementation of reading and writing literacy for class IV students at SD Negeri 1 Ngropoh Temanggung? The author uses a descriptive qualitative approach method. This research aims to describe the implementation of reading and writing literacy in class IV students at SD Negeri 1 Ngropoh Temanggung. Qualitative research data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The research results obtained in the field show that the reading and writing literacy activities carried out in class IV students at SD Negeri 1 Ngropoh Temanggung have the habit of reading and writing both inside and outside the classroom. The teacher asks students to read 15 minutes before class starts, provides a reading corner in the classroom so students can read without going to the library, gives rewards to students who have read and written a lot from a story or other, the teacher also encourages students to be interested in reading and writing by displaying audio visuals.